Studies Progression on the Function of Autophagy in Viral Infection - Liang, Weizheng; Liu, Huimin; He, Junli; Ai, Lisha; Meng, Qingxue; Zhang, Weiwen; Yu, Chengwei; Wang, Hao; Liu, Hui (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is a conservative lysosomal catabolic pathway commonly seen in eukaryotic cells. It breaks down proteins and organelles by forming a two-layer membrane structure of autophagosomes and circulating substances and maintaining homeostasis. Autophagy can play a dual role in viral infection and serve either as a pro-viral factor or an antiviral defense element dependent on the virus replication cycle. Recent studies have suggested the complicated and multidirectional role of autophagy in the process of virus infection. On the one hand, autophagy can orchestrate immunity to curtail infection. On the other hand, some viruses have evolved strategies to evade autophagy degradation, facilitating their replication. In this review, we summarize recent progress of the interaction between autophagy and viral infection. Furthermore, we highlight the link between autophagy and SARS-CoV-2, which is expected to guide the development of effective antiviral treatments against infectious diseases.